Transparent Nacre‐like Composites Toughened through Mineral Bridges. (20th May 2020) - Magrini, Tommaso; Moser, Simon; Fellner, Madeleine; Lauria, Alessandro; Bouville, Florian; Studart, André R.
Abstract: Bulk materials with remarkable mechanical properties have been developed by incorporating design principles of biological nacre into synthetic composites. However, this potential has not yet been fully leveraged for the fabrication of tough and strong materials that are also optically transparent. In this work, a manufacturing route that enables the formation of nacre‐like mineral bridges in a bioinspired composite consisting of glass platelets infiltrated with an index‐matching polymer matrix is developed. By varying the pressure applied during compaction of the glass platelets, composites with tunable levels of mineral bridges and platelet interconnectivity can be easily fabricated. The effect of platelet interconnectivity on the mechanical strength and fracture behavior of the bioinspired composites is investigated by performing state‐of‐the‐art fracture experiments combined with in situ electron microscopy. The results show that the formation of interconnections between platelets leads to bulk transparent materials with an unprecedented combination of strength and fracture toughness. This unusual set of properties can potentially fulfill currently unmet demands in electronic displays and related technologies. Abstract : The interconnectivity of glass platelets‐reinforced scaffolds can be fine‐tuned during the fabrication of bulk transparent nacre‐like composites. The high density of strong mineral connections leads to the unusual combination of high strength and high toughness within bulk structural composites that are made transparent by refractive index matching between the reinforcing elements and the organic matrix.